Corporate Governance Disclosure Practices And Firm Performance: The Case Of Asean - Seow, Wen Soon (2022)
This study examines the relationship between various corporate governance practices and boardroom diversity and firm performance among the top 98 public listed companies in 5 ASEAN countries. The firm performance is measured by return on assets (ROA) and Tobin’s Q Ratio. Ind ependent variable tested will be percentage of independent directors, Number and Presence of key corporate committees, percentage of women in board, board meeting attendance, CEO duality and board size. The sample size of this study is based on the winners countries. of ACGS 2019 of the 5 ASEAN The research uses descriptive analysis, correlation matrix and panel data analysis. The analyses performed using SPSS and Stata. Overall, the research found that the measure variables have no significant impact to th e firm performance. It suggests future researchers to explore in other factors as well as different measurements that could possibly affect the firm performance.